6 feet apart but working together. Issue 4 (31st March 2021) - Redlinger‐Grosse, Krista; Anderson, Kimberly; Birkeland, Laura; Zaleski, Christina; Reiser, Catherine
Abstract: Prior to COVID‐19, the field of genetic counseling was responding to a workforce shortage in patient‐facing roles through efforts to increase the training capacity within existing programs, as well as development of new programs. These efforts were hindered by the number and capacity of fieldwork training sites. COVID‐19 heightened this barrier with a sudden restriction on student training for an indefinite period of time. The onset of these restrictions highlighted the need to think creatively and, more importantly, collaboratively for ways to not only expand but also maintain fieldwork training capacity. Described here are two different collaborative efforts in response to pandemic‐related cancellations of important curriculum components: 1) the development of clinical simulation experiences and coursework shared between two ACGC accredited training programs; and 2) the creation of a virtual laboratory curriculum between an ACGC accredited training program and a non‐academic laboratory partner. This Professional Issues paper illustrates how collaboration with our academic and non‐academic colleagues benefits students, training programs and non‐academic partners beyond the needs of the initial crisis of a global pandemic.